The Changing Face of Economic and Management Education: Students’ Perspectives and Expectations in the Context of Green Transition (on the Example of the Faculty of Management and Business, University of Prešov) - Huttmanová, Emília; Chovancová, Jana; Adamišin, Peter; Mikča, Radoslav (Publishing House of Wroclaw University of Economics and Business, 2025)
Economic education is shaped by global environmental and social changes. There is growing pressure to modernise the content and delivery of higher education in economics to prepare graduates for the labour market with the skills to face current and future challenges. This paper examines the attitudes of Bachelor’s degree students in economics and management at the Faculty of Management, Economics and Business regarding the inclusion of green and sustainability topics in the curriculum. A questionnaire survey revealed that while students are interested in sustainability, they expect more focus on practical applications. The paper also presents approaches to integrating green topics using two newly accredited programmes that apply participatory and innovative teaching methods.
Quote as: Huttmanová, E., Chovancová, J., Adamišin, P. & Mikča, R. (2025). The Changing Face of Economic and Management Education: Students’ Perspectives and Expectations in the Context of Green Transition (on the Example of the Faculty of Management and Business, University of Prešov). In B. Drelich-Skulska, M. Sobocińska, & A. Tomášková (Eds.), Sustainable Development in Light of Research by Scientists from Poland, Czechia and Slovakia. Different Research Perspectives (pp. 31-46). Publishing House of Wroclaw University of Economics and Business.
Keywords: education; study programmes; green topics; sustainability; questionnaire survey